Development of Thermal Sensor by Reinforced Graphene Nanoplatelets Thermoplastic Blends. Issue 5 (24th March 2018) - Sharma, Ajay; Pandey, Mayank; Khutia, Moumita; Joshi, Girish M.; Cuberes, M. Teresa
ABSTRACT: Polymer composites made of carbon allotropes were highly crucial for various engineering applications. We demonstrated the successful modification of polyacrilonitrile/polyvinylfloride blends by reinforced graphene nanoplatelets. The atomic force microscopy confirms the partial immiscible traces of polymer systems with asperities on the surface of the modified blends due to loading of graphene. The phase angle (Ɵ) measurement across the temperature (40–150°C) with the broadband frequency (50–35 MHz) is performed using the impedance analyzer. The results demonstrated the decrease in phase angle as a function of temperature. This investigation is highly suitable for the development of thermal sensor for engineering and health applications. GRAPHICAL ABSTRACT: